The effect of remittances on crime in India - Malvika Mahesh (IZA Journal of Labor Policy, 2020)
There is a well-established literature that finds a strong causal association between remittance flows and economic growth and poverty. Owing to the poverty-alleviating and income-generating effects of remittances, it may theoretically reduce crime by increasing the opportunity cost of committing crime. This paper studies the effects of remittance receipts on crime outcomes in India. The identification strategy, exploits the variation in rainfall as an instrument for remittance receipts. The results suggest that remittance receipts have a negative effect on violent crimes and a positive effect on nonviolent crimes. Since remittance flows mean that more economic resources are available, remittances provide an incentive for certain crimes that thrive in the presence of economic resources. Therefore, an important implication of this result is that as remittance receipts increase income and welfare, there is a diverse effect on the costs and benefits of different types of crimes. It may result in unfavorable outcomes in the form of increases in certain nonviolent crimes.
Keywords: F22; F24; 330; crime; remittance receipts; income